What’s in a name? James Burbage and his Playhouse - Moseley, C.W.R.D. (Early Modern Culture Online, 2018)
The choice of the name ‘The Theatre’ for the new purpose built structure in Shoreditch in 1576 was not an obvious one. This paper will speculate about why it was chosen, and what ideas and values that word would have communicated to its customers. I shall also very briefly glance at what we know of the basic structure of the building, and speculate about why that shape and not another was used. Possible links to early anatomy theatres will be suggested. How far the ideas contained in the structure and the name might have affected the reception of plays is worth at least some consideration, and I hope one day to develop the ideas of the paper into a fuller study of how early audiences watched as well as heard.